2021
DOI: 10.1002/emp2.12388
|View full text |Cite
|
Sign up to set email alerts
|

Understanding patients’ end‐of‐life goals of care in the emergency department

Abstract: Funding and support: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…[13][14][15] Furthermore, much of the available emergency care research regarding older adults' patient-centered goals currently focuses on treating clinicians performing end-of-life goals of care conversations. [16][17][18] However, ED treating clinicians are tasked with navigating older adult priorities not just during critical illness or end of life.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Furthermore, much of the available emergency care research regarding older adults' patient-centered goals currently focuses on treating clinicians performing end-of-life goals of care conversations. [16][17][18] However, ED treating clinicians are tasked with navigating older adult priorities not just during critical illness or end of life.…”
Section: Introductionmentioning
confidence: 99%
“…Provision of end-of-life care in the ED is fraught with challenges [ 11 , 38 ]. Emergency medicine training often adopts a “save-all” mentality.…”
Section: Discussionmentioning
confidence: 99%
“…End-of-life care in the ED is rapidly gaining importance as the ageing population increases globally [ 10 , 11 ]. However, existing literature provides limited information regarding patients’ and families’ experiences of ED end-of-life management [ 12 ], and perspectives and barriers experienced by ED and community healthcare professionals [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The whole group of patients aged 70 years or older had a median of three comorbidities and a median clinical frailty score of three. It would have been relevant to have had conversations about values and preferences with more patients from this group, as research has shown discordance between physicians’ assessment of patient goal of care with the patients’ own goals of care [ 41 ]. The current study aimed to explore the levels of limitation decisions and shared decision-making, but in future studies, it will be relevant to include patient involvement in decisions about full treatment, including transfer to an ICU.…”
Section: Discussionmentioning
confidence: 99%